Exploration geophysics - Gadallah, Mamdouh R. (Springer-Verlag, 2010)
Overview of geophysical techiniques -- Seismic fundamentals -- Data acquisition -- Seismic data processing -- Seismic interpretation -- 4-D (time lapse 3-D) seismic surveys -- Future trends.